Carbon Dioxide Absorption into Aqueous Blends of Potassium Carbonate and Amine - Kim, Y.E.; Choi, J.H.; Nam, S.C.; Yoon, Y.I. (Asian Journal of Chemistry, 2012)
In this study, amines were added to aqueous K2CO3 solution as a promoter to improve absorption rate. The CO2 equilibrium partial pressure (PCO2*) and the absorption rate were measured using vapour-liquid equilibrium (VLE) equipment at the 313, 333 and 353 K condition of flue gas. Results showed that K2CO3/ethylenediamine (EDA), K2CO3/diethylenetriamine (DETA), K2CO3/triethylenetetramine (TETA), K2CO3/tetraethylenepentamine (TEPA) solutions had CO2 equilibrium partial pressure lower than that of monoethanolamine solution at 313 K. In addition, it was found that ethylenediamine was the most effective promoter to increase the absorption rate of aqueous K2CO3 solution.